Implementation of The Policy on The Distribution of Village Operational Funds as an Instrument of Good Governance in The Government of Sorong City - Zenny Elisabeth Ramschie; Munawar Noor; Aris Toening W (International Forum of Researchers and Lecturers, 2026)
This study aims to analyse the implementation of the Village Operational Funds (VOF) distribution policy as an instrument for realising good governance principles in the Government of Sorong City. The research focuses on the implementation of fund distribution and the application of transparency, accountability, participation, and effectiveness in managing Village Operational Funds. A quantitative approach with a descriptive design was employed. Data were collected through questionnaires administered to 20 respondents and in-depth interviews with five key informants, including village officials and local government representatives. Additional data were obtained through observations of planning and fund utilisation processes, as well as through analysis of regulatory documentation and accountability reports. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the Village Operational Funds distribution policy in Sorong City has not been carried out in accordance with existing regulations, particularly regarding administrative procedures and fund disbursement mechanisms. This condition is primarily caused by the absence or non-disbursement of operational funds at the village level. Furthermore, the application of good governance principles has not been fully optimised due to limited human resources, weak supervision, and low community participation in planning and evaluation. The study concludes that Village Operational Funds have strategic potential as an instrument for promoting good governance if managed transparently and accountably. Therefore, strengthening institutional capacity, supervision systems, and community participation is essential to support effective village governance in Sorong City.